Persian religion in the Achaemenid period = La religion perse à l'époque achéménide - Henkelman, Wouter; Redard, Ćeline (Wiesbaden : Harrassowitz Verlag, 2017)
Includes twelve English, French, and German papers originally presented at a colloquium convened by Jean Kellens at the Collège de France (2013), this volume addresses a range of issues relating to Persian religion at the time of the Achaemenid Empire (550-330 BCE). Moving away from the reductive question whether the Achaemenid kings were Zoroastrians or not, the contributors have tried to focus either on newly identified or recently published sources (Central Asian archaeological finds, Elamite texts and seal impressions from the Persepolis Fortification Archive, Aramaic texts from Bactria, the Persepolis Bronze Plaque), or on current (and ongoing) debates such as the question of the spread of the so-called long liturgy to Western Iran. In doing, different perspectives are chosen: whereas some have stressed the Iranian or Indo-Iranian tradition, others have pointed out the importance of the Elamite and Assyro-Babylonian contexts. At the same time, the volume shows a broad agreement in its insistence on the essential position of primary sources, problematic as they may be, and on the important role the Achaemenid rulers and the imperial project played in the evolution of Iranian religion.
Les Achéménides entre textes et liturgie avestiques / Jean Kellens -- La liturgie longue en langue avestique dans l'Iran occidental / Alberto Cantera -- Liturgies and calendars in the politico-religious history of pre-Archaemenian and Achaemenian Iran / Antonio Panaino -- Religious aspects in the Aramaic texts from Bactria / Jan Tavernier -- State theology and royal ideology of the neo-Assyrian empire as a structuring model for the Achaemenid imperial region / Salvatore Gaspa -- Beyond Auramazda and the winged symbol: imagery of the divine and numinous at Persepolis / Mark B. Garrison -- Die ikonographische Angleichung von Gott und König in der achämenidischen Kunst / Bruno Jacobs -- Humban & Auramazda: royal gods in a Persian landscape / Wouter F.M. Henkelman -- Of Gods and men in the Persepolis Bronze Plaque / Gian Pietro Basello -- Achaemenid "ritual architecture": reflections on the elusive archeological evidence of the religion of the Achaemenids / Pierfrancesco Callieri -- Sanctuaires sogdiens et cultes avestiques de l'époque de Gava à l'époque hellénistique / Claud Rapin -- <<... how median the Medes were>>? État d'une question longuement débattue / Adriano V. Rossi.
International conference proceedings from an international colloquium on Achaemenid religion, held at the Collège de France, November 17-18, 2013.
Includes bibliographical references.
Contributed volume with 7 English and 4 French contributions, 1 German contribution; preface in English.
Print version record.
JSTOR
Keywords: Achaemenid dynasty, -- 559-330 B.C. -- Congresses; Achaemenid dynasty, -- 559-330 B.C.; Iran -- Religion -- Congresses; Iran -- History -- To 640 -- Congresses; Iran -- Civilization -- To 640 -- Congresses; Iran -- Antiquities -- Congresses; Art and religion -- Iran -- History -- To 1500 -- Congresses; Gods in art -- Congresses; Art, Ancient -- Iran -- Congresses; Religion and politics -- Iran -- Congresses; Iran -- Religion -- Congrès.; Iran -- Histoire -- Jusqu'à 651 -- Congrès.; Iran -- Civilisation -- Jusqu'à 651 -- Congrès.; Iran -- Antiquités -- Congrès.; Dieux dans l'art -- Congrès.; Art antique -- Iran -- Congrès.; Religion et politique -- Iran -- Congrès.; RELIGION -- Zoroastrianism; Antiquities; Art, Ancient; Art and religion; Civilization; Gods in art; Religion; Religion and politics; Iran; Religion; Iran; To 1500; Conference papers and proceedings; History